2016
DOI: 10.1007/s00248-016-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Fungal Communities to Elevated CO2

Abstract: Soil filamentous fungi play a prominent role in regulating ecosystem functioning in terrestrial ecosystems. This necessitates understanding their responses to climate change drivers in order to predict how nutrient cycling and ecosystem services will be influenced in the future. Here, we provide a quantitative synthesis of ten studies on soil fungal community responses to elevated CO2. Many of these studies reported contradictory diversity responses. We identify the duration of the study as an influential para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…Elevated CO 2 can promote mycorrhizal colonization of plant roots as a consequence of the enhanced carbon allocation to roots ( Zhu et al, 2016 ; Asha et al, 2017 ), which may result in an increased mineral uptake from soil but not necessarily correlated with nutrient transfer to the host plant ( Smith and Read, 2008 ). Regarding the community composition of AMF, elevated CO 2 increased the ratio of Glomeraceae to Gigasporaceae but this effect may be masked by the natural changes through time ( Cotton et al, 2015 ) and also by the dependency of different fungi on water availability and precipitation ( Veresoglou et al, 2016 ). The application of molecular tools revealed that, at present, Glomeraceae dominate the composition of the AMF communities in vineyards in Oregon (United States) ( Schreiner and Mihara, 2009 ), Piedmont (Italy) ( Balestrini et al, 2010 ) and Burgundy (France) ( Bouffaud et al, 2016 ), being the AMF diversity relatively low, which contrasts with the high diversity of AMF in the rhizosphere of European wild grapevine V. vinifera L. ssp.…”
Section: Effects Of Changing Environments On the Arbuscular Mycorrhizmentioning
confidence: 99%
“…Elevated CO 2 can promote mycorrhizal colonization of plant roots as a consequence of the enhanced carbon allocation to roots ( Zhu et al, 2016 ; Asha et al, 2017 ), which may result in an increased mineral uptake from soil but not necessarily correlated with nutrient transfer to the host plant ( Smith and Read, 2008 ). Regarding the community composition of AMF, elevated CO 2 increased the ratio of Glomeraceae to Gigasporaceae but this effect may be masked by the natural changes through time ( Cotton et al, 2015 ) and also by the dependency of different fungi on water availability and precipitation ( Veresoglou et al, 2016 ). The application of molecular tools revealed that, at present, Glomeraceae dominate the composition of the AMF communities in vineyards in Oregon (United States) ( Schreiner and Mihara, 2009 ), Piedmont (Italy) ( Balestrini et al, 2010 ) and Burgundy (France) ( Bouffaud et al, 2016 ), being the AMF diversity relatively low, which contrasts with the high diversity of AMF in the rhizosphere of European wild grapevine V. vinifera L. ssp.…”
Section: Effects Of Changing Environments On the Arbuscular Mycorrhizmentioning
confidence: 99%
“…Average AM fungal richness was higher under eCO 2 compared with aCO 2 treatments (though both treatments had equivalent total taxon pools of 51 OTUs). Previously observed increases in total fungal diversity under eCO 2 are determined by the length of the experiment (Veresoglou et al, 2016). Longer-term studies allow greater recruitment from the meta-community of taxa pre-adapted to these new environmental conditions and if sufficiently long term, the evolution of new species (Johnson et al, 2013;Veresoglou et al, 2016), both of which increase local taxa richness.…”
Section: Am Fungal Diversity In Gifacementioning
confidence: 97%
“…Previously observed increases in total fungal diversity under eCO 2 are determined by the length of the experiment (Veresoglou et al, 2016). Longer-term studies allow greater recruitment from the meta-community of taxa pre-adapted to these new environmental conditions and if sufficiently long term, the evolution of new species (Johnson et al, 2013;Veresoglou et al, 2016), both of which increase local taxa richness. At the GiFACE, the expansive semi-natural grassland surrounding eCO 2 FACE rings and the longterm experimental duration certainly provide ample opportunity for recruitment of pre-adaptive AM fungal taxa from the meta-community.…”
Section: Am Fungal Diversity In Gifacementioning
confidence: 97%
See 2 more Smart Citations